Scatological Humour and the Absent Anthropology of Privacy - Peacock, Vita (Surveillance & Society)

(untitled) (Surveillance Studies Network, 2025)
This article addresses the puzzle of scatological humour among privacy advocates. Drawing on ethnographic work in Britain in 2014 and in Germany between 2019–2023, it advances a consideration of the phenomenon as a form of “boundary play” (Nippert-Eng 2005). Deploying the transgressive exposure of behaviours of a human body, as expressive of transgressions across a social body, scatological references use satire to make statements around contemporary digital surveillance. Splicing this to a noteworthy absence of anthropological scholarship on the concept of privacy, the article positions privacy as an extrinsic concept, alive at the boundary, that struggles to travel across cultural contexts. While continuing to support the local extrinsic work that privacy performs, it suggests the need to construct stronger architectures of value around other phenomena synonymous with not being readable.